Regulation of Mitochondrial Metabolism by Mfn1 Gene Encoding Mitofusin Affects Cellular Proliferation and Histone Modification - Han Xu; Xiaoyu Zhao; Yuan Yun; Yuxin Gao; Chunjie Bo; Lishuang Song; Chunling Bai; Lei Yang; Guangpeng Li; Guanghua Su (Cells, 2025)
Mitochondria maintain cellular homeostasis through the dynamic balance of fusion and fission, which relies on nuclear-encoded mitochondrial fusion proteins, mitofusins 1 and 2 (Mfn1, Mfn2). Changes in Mfn1 and Mfn2 expression significantly affect mitochondrial fusion and fission, thereby affecting cellular metabolism. This study investigated the effect of Mfn1 expression on cell proliferation, apoptosis, and mitochondrial function by overexpressing Mfn1 (in OE-Mfn1 cells) and silencing Mfn1 using short hairpin RNA (shRNA) (in shMfn1 cells). Cell proliferation capacity, mitochondrial membrane potential, and mitochondrial ATP content were measured. To investigate the effects of Mfn1 on cellular metabolism and epigenetic modifications, the levels of metabolites α-KG, A-CoA, and SAM, as well as the levels of cellular methylation and acetylation, were detected by ELISA. Differentially expressed genes and metabolites were assessed by RNA-seq and LC-MS. This study demonstrates that alterations in Mfn1 gene expression can significantly affect mitochondrial metabolism and cell proliferation and apoptosis. In addition, Mfn1 affects the expression of genes encoding enzymes that are responsible for histone methylation and acetylation, thereby regulating these modifications. These findings provide a theoretical basis for further elucidation of the mechanisms by which Mfn1 affects cell proliferation, regulates metabolites, and modulates chromatin epigenetic modification.